Karakteristik serta Keahlian Relevan dalam Profesi Akuntan Forensik - Astutie, Yanti Puji (PERMANA, 2012)
The main objective of this paper is to gain clearer understanding of the essential traits and core skills that forensic accountants are expected to possess for the varied investigative matters for which they are retained. This paper investigated   the differences preference between four groups about characteristic and relevant skills that should possesed by forensic accountants. The four groups which held as respondents are forensic accounting practitioners, accounting academics, attorneys, and society. The paper describes in detail the key findings and identities areas for further investigation.   Survey developed by online method using surveymonkey.com. The results of the present study provide much needed guidance to educators for the development of the forensic accounting curriculum by identifying pertinent skills to accompany a program of study. Findings of the paper result indcate that practitioners and academics agree that critical thinking, unstructured problem solving, investigative flexibility, and legal knowledge are important skills of forensic accountants. Attorneys and society rated deductive analysis as less important than did academics. The groups did not differ on oral and writen communication, or composure rankings. These results show that some skills are relevant and important to the outcome of forensic accounting education.